A Manual of The Theory and Practice of Classical Theatrical Dancing (Classical Ballet) (Cecchetti Method) - Beaumont, Cyril W. 1891-1976; Idzikowski, Stanislas 1894-1977; Cecchetti, Enrico Cavaliere 1850-1928; Schwabe, Randolph (London Beaumont, 1940)
The Cecchetti method is variously defined as a style of ballet and as a ballet training method devised by the Italian ballet master Enrico Cecchetti (1850–1928). The training method seeks to develop essential skills in dancers as well as strength and elasticity. The greatest influence on the development of the Cecchetti method was Carlo Blasis. A student and exponent of the traditional French school of ballet, Blasis insisted on his students conforming to strict technical principles when learning to dance, a philosophy which Cecchetti learnt from his own teachers, who were all students of Blasis (Giovanni Lepri, Cesare Carnesecchi Coppini and Filippo Taglioni). Consequently, the key characteristic of the Cecchetti method is the adherence to a rigid training regime, designed to develop a virtuoso technique, with the dancer having a complete understanding of the theory behind the movement.The other key influences on the Cecchetti method came from his own professional career as a dancer, which exposed him to many different techniques and styles of ballet. When he began to gain a reputation as a teacher, he experimented with these various styles, fusing the best elements of each to create his own ballet technique and training system, the eponymous Cechetti method. Such was the success of Cecchetti's teaching, he is recognised as one of the key contributors to modern classical ballet, his method credited with significantly improving the teaching of classical ballet throughout Europe. Where previously ballet teaching had been haphazard and reliant on the preferences and style of the individual teacher, the Cecchetti method established the model of standardised teaching which is the basis of all professional ballet teaching today.Initially, Cecchetti passed on his method by teaching it to his pupils and professional dancers, including well known dancers of the early 20th century, such as Anna Pavlova, Alicia Markova, George Balanchine and Serge Lifar.
Originally published in 1922
Keywords: 20th Century (1901-2000); Method; Ballet